ACCELERATING ECONOMIC DEVELOPMENT IN ZAMBIA THROUGH SUCCESSFUL ENTREPRENEURSHIP: A PRAGMATIC STUDY - Imakando, Liane Moosho (International Journal For Research In Business, Management And Accounting, 2021)
There is growing pressure on the government of Zambia to provide solutions for a better future for its citizens, in particular for the youth (ZDYD, 1994). This research argues that one solution is to strengthen success amongst Small and Medium Enterprises (SMEs). A mixed method was applied and quantitative findings show that the determinants of entrepreneurship success at the entrepreneur’s internal level include personality traits i.e. alertness, strong urge to achieve, innovativeness, ability to anticipate future opportunities, ability to take risks, desire to attain economic freedom and resilience. Managerial skills include effective marketing strategies, ability to build business networks, training, access to and use of information, decision making, financial intelligence and business experience. Psycho social factors include relevant knowledge base. At the entrepreneur’s external level success factors include infrastructure i.e. energy, roads, communication and permanent buildings; favourable policies specifically SME, tax and industrial policies and supportive institutions i.e. research and training and government agencies. Qualitative findings include the need to achieve economic freedom, proper and timely use of information, adoption of new technology acquisition of business management skills, risk taking, resilience, diversification of products and services, infrastructure development, favourable policy and legal framework. Based on the findings, an integrative entrepreneurship success framework for SMEs that can if applied, accelerate Zambia’s economic development is proposed. The framework is adapted from a similar framework developed for SMEs in Malaysia.